2022
DOI: 10.1101/2022.09.26.509601
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural conservation of Lassa virus glycoproteins and recognition by neutralizing antibodies

Abstract: Lassa fever is an acute hemorrhagic fever caused by the zoonotic Lassa virus (LASV). The LASV glycoprotein complex (GPC) mediates viral entry and is the sole target for neutralizing antibodies. Immunogen design is complicated by the metastable nature of recombinant GPCs and the antigenic differences amongst LASV lineages. Despite the sequence diversity of GPC, structures of most lineages are lacking. We present the development and characterization of prefusion-stabilized, trimeric GPCs of LASV lineages II, V, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…Recent studies have shown multiple conformations of LASV's fusion peptide are possible, with unbound (whether by matriglycan or antibodies) GPCs residing flexibly in the space between the HR1a helix, HR1d helix, and the HR2 loop. 30,31 We note that binding by FP-1 seems to promote the fusion peptide conformation where residues 260-268 extend towards the interior trimeric interface, as has been observed when GPC is bound by other NAbs such as 25.10C and 37.7H. While we are yet unable to confirm, it is reasonable to suspect that FP-1 would have the potential to mature towards a neutralizing phenotype as has been reported with many GPC-B mAbs.…”
Section: Analysis Of Recombinant Lasv Gpc-induced Antibody Responses:...mentioning
confidence: 53%
See 4 more Smart Citations
“…Recent studies have shown multiple conformations of LASV's fusion peptide are possible, with unbound (whether by matriglycan or antibodies) GPCs residing flexibly in the space between the HR1a helix, HR1d helix, and the HR2 loop. 30,31 We note that binding by FP-1 seems to promote the fusion peptide conformation where residues 260-268 extend towards the interior trimeric interface, as has been observed when GPC is bound by other NAbs such as 25.10C and 37.7H. While we are yet unable to confirm, it is reasonable to suspect that FP-1 would have the potential to mature towards a neutralizing phenotype as has been reported with many GPC-B mAbs.…”
Section: Analysis Of Recombinant Lasv Gpc-induced Antibody Responses:...mentioning
confidence: 53%
“…27,28 Since then, methods have been described to stabilize the trimeric conformation of prefusion GPC in the absence of a trimer-stabilizing mAb. [29][30][31] We previously demonstrated that prefusion GPC trimers are stabilized by genetic fusion to the trimeric scaffold I53-50A. 30,31 These fusion proteins, known as GPC-I53-50A, have not only proven to be a useful reagent for characterizing and isolating GPC-specific antibodies but also were able to induce NAb responses in rabbits.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations